2017
DOI: 10.1002/pmh.1365
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the road from childhood adversity to personality disorder: The role of unresolved states of mind

Abstract: Childhood adversity has been found to be an important aetiological factor in the development of personality disorder (PD) in several studies. However, the role of disorganized attachment with unresolved mental states for traumatic experiences requires further investigation. This study explores the relationship between childhood adversities, unresolved states of mind, PD diagnosis and psychiatric distress. Two hundred forty-five adult participants, 124 from a clinical PD group and 121 non-psychiatric controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…In this regard, although the parent-child attachment develops in the early years of life [11], it does continue to influence the individuals' psychological adjustment throughout adolescence [12,13]. Indeed, attachment and the subsequent attachment-related experiences play a pivotal role in promoting mental health issues in adolescence as well as adulthood [14,15].…”
Section: Adolescence Attachment To Parents and Adjustment Difficultiesmentioning
confidence: 99%
“…In this regard, although the parent-child attachment develops in the early years of life [11], it does continue to influence the individuals' psychological adjustment throughout adolescence [12,13]. Indeed, attachment and the subsequent attachment-related experiences play a pivotal role in promoting mental health issues in adolescence as well as adulthood [14,15].…”
Section: Adolescence Attachment To Parents and Adjustment Difficultiesmentioning
confidence: 99%
“…One crucial limitation is that we did not assess attachment styles in any of our samples, although our results can be interpreted to draw some preliminary conclusions and inspire future research. First of all, previous results show the relationship between a disorganized attachment and a higher probability of suffering anxiety (86), depression (87), addiction (88), or PTSD (89), and expressing personality disorders such as borderline, avoidant, or antisocial, among others (90). In turn, recent research has shown an association between insecure attachment, alcohol/substance addiction, and an increased amount of borderline personality organization (57).…”
Section: Discussionmentioning
confidence: 98%
“…Winnicott y Balint ya advirtieron sobre el uso peculiar de las interpretaciones que hacían estos pacientes y de su nula eficacia. Sin embargo, la integración de estados mentales irresueltos es uno de los objetivos principales de la terapia (Cirasola et al, 2017;Crittenden y Newman, 2010), y la interpretación es una herramienta que pone en relación aspectos no relacionados previamente, posee gran potencial integrador. Existe evidencia de que la eficacia de las interpretaciones no se asocia sólo al contenido de las mismas, también deben tener en cuenta los procesos, es decir, el hecho de que una interpretación es un acto que ejerce sus efectos en el contexto de una relación interpersonal (Caspar et al, 2000).…”
Section: Secuenciación Y Parsimoniaunclassified